Wilhelm Uhthoff and Uhthoff's phenomenon. (November 2020) - Jain, Aarushi; Rosso, Mattia; Santoro, Jonathan D
Wilhelm Uhthoff, known for his contributions to both neurology and neuro-ophthalmology, was a German ophthalmologist who specialized in neurologic disorders. The eponym "Uhthoff's phenomenon" was first used to describe the reversible, transient blurring of vision in patients with multiple sclerosis during exercise. Subsequently, it was discovered that this neurologic sign not only was triggered by physical exertion but also by other homeostatic disruptions such as hot baths, menstruation, and high external temperatures. Here, we take a look at the life and career of Wilhelm Uhthoff and discuss the basis behind this phenomenon.